Transvaginal sonographic cervical length assessment in predicting the outcome of induction of labor - Sreenivas, Anju; Geetha, K.; Subhashini, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The aim of the study was to assess Bishop Score in women undergoing induction of labor followed by cervical length measurement by transvaginal sonography and to study the role of transvaginal sonographic cervical assessment in predicting outcome of induction of labor. Methods: This was a prospective observational study carried out in 300 pregnancy women undergoing induction of labor. In all the women, Bishop score was calculated by per vaginal examination and cervical length assessed by transvaginal ultrasound, both prior to induction of labor Results: This study has demonstrated that in singleton pregnancies undergoing induction of labor at 37-41 weeks of gestation, successful vaginal delivery within 24hrs of induction occurred in 66.8%. The study has also demonstrated that induction to delivery interval is significantly associated with both the preinduction Bishop score and sonographically measured cervical length, higher the Bishop score and lesser the cervical length, better the likelihood of vaginal delivery within 24 hrs of induction. The best cutoff point for successful induction was ≥3 for Bishop score and ≤2.5 cm for cervical length, which was obtained from the ROC curve. Conclusions: Cervical length assessment by transvaginal ultrasound was a better predictor of successful induction of labor.